DETERMINAN KOMPETENSI TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK WILAYAH TANGERANG - Widayat, Widayat (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Employees must have high performance, why? because serving the community must be with heart, how to be careful, and wholeheartedly. People don't see shabby or grand buildings, they just want to be civilized. Performance of services in the tax office must be a priority, because of that capital awareness of the public to pay taxes. This study wanted to explore information about the performance of tax service employees in the Tangerang region. How is the role of individuals and organizations in creating services. Quantitative research is seen as more effective in terms of time. Therefore, regression analysis was chosen to analyze the data. Data obtained through a questionnaire. The findings show evidence, ability is a major factor in tax service. Knowledge, expertise and experience about taxes is a preference in service. Of course this is inseparable from many factors, among them Educational background, training, and experience